2015
DOI: 10.1177/1557988315623993
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Manifestations of Depression and Help Seeking Among Men

Abstract: Men who do not seek help for mental health problems may experience unnecessary suffering which ultimately affects the well-being of themselves and others. Gendered manifestations of depressive symptoms may play an important role in why some men do not seek help for mental health issues. Using data from 2,382 male respondents in the National Comorbidity Survey Replication, the authors examined the relationship that both traditional and male-typical symptoms of depression had on the help-seeking behaviors of men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 43 publications
(78 reference statements)
3
82
1
Order By: Relevance
“…In a socio-cultural environment that celebrates a strong and stoic masculinity, being able to selectively engage certain monologic traits mitigated social marginalization and emphasized the "positive qualities and resourcefulness" (Coen et al, 2013, p. 99) of a more traditional masculinity. These findings contrast somewhat with the Call and Shafer (2015) research, which suggests that men with a more traditional masculinity are more likely to exhibit non-DSM symptoms, and men with a less traditional, or dialogic masculinity, are more likely to present with DSM-5 symptoms. Coen et al's (2013) findings suggest that the mechanisms that drive symptomatology and help seeking are complex, not necessarily predictable, and are strongly linked to the socio-cultural milieu within which men live.…”
Section: Expression Of Non-dsm Symptomatologycontrasting
confidence: 85%
See 2 more Smart Citations
“…In a socio-cultural environment that celebrates a strong and stoic masculinity, being able to selectively engage certain monologic traits mitigated social marginalization and emphasized the "positive qualities and resourcefulness" (Coen et al, 2013, p. 99) of a more traditional masculinity. These findings contrast somewhat with the Call and Shafer (2015) research, which suggests that men with a more traditional masculinity are more likely to exhibit non-DSM symptoms, and men with a less traditional, or dialogic masculinity, are more likely to present with DSM-5 symptoms. Coen et al's (2013) findings suggest that the mechanisms that drive symptomatology and help seeking are complex, not necessarily predictable, and are strongly linked to the socio-cultural milieu within which men live.…”
Section: Expression Of Non-dsm Symptomatologycontrasting
confidence: 85%
“…Men who endorse and identify with traditional male norms of self-reliance and control may be more likely to feel that their depressive experience, and the act of help seeking, is in opposition with their masculine identities (Call & Shafer, 2015). On the other hand, men who identify with a more nuanced masculinity may more quickly engage in coping behaviours such as seeking help from a social or professional support (Call & Shafer, 2015, Rice et al, 2015. The principal mechanism underlying this process appears to relate to control.…”
Section: Chapter Iv: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also revealed that men are quite often reluctant to seek emotional or psychological support, mainly due to masculine norms emphasizing the importance of self-sufficiency, strength, and invulnerability (Call and Shafer 2015;Vogel and Heimerdinger-Edwards, Hammer and Hubbard 2011). However, promising results have been reported by studies on various programs and work targeted to fathers in need of support.…”
Section: Fathers In Child Welfare: Lessons From the Recent Researchmentioning
confidence: 94%
“…The exclusion criteria were the following: age under 18 jears, age over 65 years, pregnancy and postpartum, mental retardation or intellectual disability. Patients over 65 were excluded since it was shown that screening methods available are less robust for this age group and symptoms of depression often coexist with medical comorbidities [25,26]. We excluded 14 patients who had an appointment with a psychiatrist before the study began and four who had not filled out the questionnaire.…”
Section: Patients and Settingmentioning
confidence: 99%